The battle over homework common ground for administrators, teachers, and parents - Cooper, Harris M.; Sage eBooks (Thousand Oaks, Calif. : Corwin, 2007)
The author provides educators with terms, definitions, and updated research to hold constructive conversations with students, their families, and the community. Administrators teachers, and parents can collaborate to make sound decisions about homework policies and guidelines.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Homework; Electronic books